Responses to the Publication of the American Psychiatric Association's DSM-5. (November 2017) - Kinderman, Peter; Allsopp, Kate; Cooke, Anne
The idea and practice of diagnosis in psychiatry has always been controversial. Controversy came to a head in the period preceding and immediately after publication of the latest version of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders–Fifth edition . There was widespread international discussion and debate not only in scholarly journals but in mainstream and social media, and to the formation of International DSM Response Committee and an International Summit on Psychiatric Diagnosis. This article documents that process and outlines the issues that provoked, and continue to provoke most controversy, from the (admittedly personal) perspective of those involved. It ends with suggestions of alternatives to diagnosis, which avoid some of these problems and outlines how these are being taken forward. The next 10 years are likely to see significant change.